ANALISIS PEMANFAATAN MATH GAMES BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWA DI SEKOLAH DASAR - Haidir, Haidir; Nuria, Sarda; Irnanda, Ela; Darmansyah, Darmansyah; Fitria, Yanti (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
Mathematics is a field of science that is used in everyday life. Mathematics is applied to almost aspects of life science. Mathematics is the queen of science. Many people assume that Mathematics is difficult. That's why Mathematics is considered scary, especially for children, especially elementary school students. To attract students' attention, Mathematics learning is carried out by utilizing Android-based games as a learning media. The research method applied is quantitative through literature study. The Android-based educational game can help improve students' critical thinking skills. So it can be concluded that this educational game proves that Android-based educational game is useful for students because this educational game is a tool to help students learn and can help increase students' interest in learning.